Upaya Single Parent dalam Menanamkan Pendidikan Akhlak Bagi Anak di Desa Arga Jaya Kecamatan Air Rami - Intan Kurnia Sari; Qalbi Khairi; Hamdan Efendi (GHAITSA : Islamic Education Journal, 2024)
Single parents must train children to worship, and instill morals in children in accordance with the teachings in religion, namely practices that connect humans with their God. Children must be accustomed to behaving politely towards parents and other people, therefore the role of single parents is very important for children's moral education. This study aims to determine the efforts of single parents towards children's moral education and the inhibiting factors of single parents' efforts towards children's moral education. This study uses data collection techniques of observation, interviews, and documentation. Interviews were conducted with single parents (single parent), and children related to single parent efforts on children's moral education. Observation and documentation are carried out on matters relating to the efforts of single parents on children's moral education. Based on the results of the study, the efforts of single parents towards children's moral education, single parents (single parents) in Arga Jaya Village, Air Rami District, namely single parents (single parents) have not perfectly carried out their role in providing moral education to children. Due to the level of education and knowledge of single parents (single parent) is still low. Therefore, the efforts made by single parents have not been effective in providing moral education to children. While the inhibiting factors of single parents' efforts on children's moral education consist of: as single parents, they have great difficulty if they do not have a husband, the difficulties experienced in dividing time to educate children and work.